To the Core of Autocatalysis in Cyclohexane Autoxidation - Hermans, Ive; Jacobs, Pierre A.; Peeters, Jozef (Chemistry : a European journal, 2006)
Despite their industrial importance, the detailed reaction mechanism of autoxidation reactions is still insufficiently known. In this work, complementary experimental and theoretical techniques are employed to address the radical‐chain initiation in the autoxidation of cyclohexane with a particular focus on the “lighting‐off” of the oxidation by (added) cyclohexanone. We used a newly developed method to quantify the intrinsic rate of chain initiation as well as the rate enhancement by cyclohexanone and several other (oxygenated) molecules. On the basis of first principles, the hitherto assumed perhemiketale mechanism was found to be many orders of magnitude too slow to account for the observed initiation enhancement by the ketone. Instead, it is shown that the pronounced chain‐initiation enhancement by the ketone is attributable to a newly proposed concerted reaction between cyclohexyl hydroperoxide and cyclohexanone, in which the .OH radical breaking away from the hydroperoxide s an αH atom from the ketone, thereby energetically assisting in the cleavage of the ROOH bond. This reaction is highly efficient in generating radicals as it quasi‐excludes geminate in‐cage recombination. As a result, the ketone oxidation product at a level of 1 mol % increases the initiation rate by one order of magnitude, and so acts as a highly efficient “autocatalyst” in autoxidation reactions. An analogous reaction with cyclohexanol, although estimated to be even faster, has only a marginal effect on the overall kinetics, owing to the fast subsequent formation of HO2. radicals that very rapidly terminate with other ROO. radicals. Finally, solid evidence is presented that, also in absence of oxygenates, ROOH initiation is actually a bimolecular reaction, involving concerted H ion from the alkane substrate by the nascent .OH. The .OH radical breaking away from dissociating cyclohexyl hydroperoxide can an αH atom from cyclohexanone in a concerted, low‐barrier reaction. Compared with homolytic dissociation, the stabilized ketonyl and cyclohexoxy radical, hydrogen‐bonded to H2O, are forced apart by the energy drop after the transition state, thus contributing to the high initiation efficiency of this newly discovered reaction (see scheme).